Overexpression of chaperonin containing T-complex polypeptide subunit zeta 2 (CCT6b) suppresses the functions of active fibroblasts in a rat model of joint contracture - Xiaoyou Yi; Zhe Wang; Jianhua Ren; Ze Zhuang; Kaihua Liu; Kun Wang; Ronghan He (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Joint contracture is a fibrous disease characterized as joint capsule fibrosis that results in joint dysfunction and disability. The purpose of this study was to analyze the biological activities of chaperonin containing T-complex polypeptide (CCT) subunits and to determine the role of CCT chaperone in joint contracture in a rat model. Methods In this study, the rat model of joint contracture was established by immobilizing the rat knee for 8 weeks. Then, fibroblasts were isolated from the posterior joint capsule and were cultured for functional analysis such as qRT-PCR, Western blot, transwell assay, and collagen assay. The effect of CCT subunit was determined by employing a lentivirus containing target gene and transfecting it into fibroblasts. Results Results of qRT-PCR and Western blot showed that among all CCT subunits, CCT6b significantly decreased in the fibroblasts from contractive joints compared to cells from normal joints (p < 0.05). Overexpression of CCT6b by transfection of lentivirus containing CCT6b gene to active fibroblasts significantly inhibited fibrous marker (α-SMA, COL-1) expressions, fibroblast migration, and collagen synthesis (all p < 0.05). Moreover, fibrosis-related chaperone CCT7 expression was decreased with CCT6b overexpression (p < 0.05). Conclusion The biological activities of CCT subunits in fibroblasts from the joint contracture rat model were analyzed in this study. CCT6b significantly decreased in the active fibroblasts, and overexpression of CCT6b significantly inhibited fibroblast functions. These findings indicate that CCT6b appears to be a potential molecular biomarker and therapeutic target for the novel therapies of joint contracture.